Three modes of heterochrony explain lobule diversity in Radula subgenus Cladoradula (Porellales: Jungermanniopsida), a small lineage of early land plants today. (5th September 2013) - Renner, Matt A. M.; Devos, Nicolas; Brown, Elizabeth A.; von Konrat, Matt J.
Abstract : Changes in lobule morphology in Radula subgenus Cladoradula show liverworts have the capacity for dramatic, relatively rapid morphological change by heterochrony. In individuals of R. bipinnata, R. boryana and R. tenax, lobules on secondary and tertiary shoots are progenetic with respect to lobules on primary shoots, in that the slope of the relationship between growth duration and shape does not change. However, in R. campanigera, lobules on secondary and tertiary branches exhibit different slopes from primary branches, but have the same growth duration, a pattern consistent with neoteny. The trajectory of allometric growth is extended or truncated in different species compared with outgroup and ancestral nodes. Changes in duration of lobule growth explain 85% of variation in lobule shape between species. Species are related by relatively shallow nodes in the crown of the Radula subgenus Cladoradula clade, suggesting that divergence and associated heterochronic changes have occurred relatively recently. The rapid morphological diversification in the crown contrasts with the relative stasis between the ancestral node and R. brunnea, the outgroup used in this analysis. A robust primary axis may be required to hold shoots away from vertical surfaces to maximize light interception, and hypermorphosis in lobule ontogeny could be a by‐product of the longer growth durations required to build axes sufficiently large to perform this structural role. Alternatively, the large auriculate lobules could function in external water transport systems by providing continuity of surfaces for solute transport via capillary action. © 2013 The Linnean Society of London, Botanical Journal of the Linnean Society, 2013, 173, 153–175.